2022
DOI: 10.1037/dev0001424
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the future in adolescence predict depressive symptoms in adolescence and early and middle adulthood.

Abstract: The current longitudinal study examined the predictive associations between the development of future perceptions in adolescence and depressive symptoms in adolescence and early and middle adulthood. Participants (N = 1,527; 48.3% female; broadly representative of Western Germany with respect to race/ethnicity and socioeconomic status) were measured yearly in adolescence at the age of 12 to 16 years and then in adulthood at the age of 35 and 45. Future perceptions were assessed during adolescence, whereas depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Such work supports the suggestion that capturing how adolescents mature and develop during adolescence may be critical to understanding their later life outcomes (Hill et al, 2019 ). Moreover, this study provides further evidence for the role of individual changes in traits and competencies during adolescence as predictors of later health adult outcomes (Allemand et al, 2022 ; Steiger et al, 2014 ).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Such work supports the suggestion that capturing how adolescents mature and develop during adolescence may be critical to understanding their later life outcomes (Hill et al, 2019 ). Moreover, this study provides further evidence for the role of individual changes in traits and competencies during adolescence as predictors of later health adult outcomes (Allemand et al, 2022 ; Steiger et al, 2014 ).…”
Section: Discussionmentioning
confidence: 56%
“…Multiple studies have now demonstrated how changes during adolescence predict later adult outcomes, including social functioning (Allemand et al, 2015 ) and depression (Allemand et al, 2022 ; Steiger et al, 2014 ). Past work with the current study sample, for instance, has focused on self-control tendencies during adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…Suffering from excessive or chronic anxiety can have a lasting impact on their mental health [ 46 ]. CRFA could be an early warning sign for the development of anxiety and depression in the years ahead [ 16 ]. The present study suggests that boosting the resilience factor working memory updating (and other executive functions; [ 47 ]) and reducing the risk factor repetitive negative thoughts (and other maladaptive strategies of emotion regulation) should be active ingredients of programs designed to prevent or alleviate children’s anxious reactions to future epidemics and related macro-level events.…”
Section: Discussionmentioning
confidence: 99%
“…Under these circumstances they are less inclined to recognize opportunities because they are preoccupied by the risks which, in their view, strongly predominate. In a large longitudinal study, adolescents’ pessimistic perceptions of the future predicted depressive symptoms 20 to 30 years later in middle adulthood [ 16 ]. Although research on future related anxiety related to epidemics and other disasters is limited, theoretical and empirical reasons concur that anxious perceptions of the future may contribute to a restriction of educational, career, and life choices in youth [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Youth with pronounced future anxiety who behave in a wait-and-see manner limit their personal and educational aspirations ( Zaleski, 1996 ; Seiffge-Krenke et al, 2012 ). Longitudinal evidence suggests that adolescents’ level of future anxiety predicted their depressive symptoms at age 35 and 45 in a large representative study ( Allemand et al, 2022 ). Based on his theoretical work, Zaleski (1996) developed the Future Anxiety Scale for adults and condensed it into the Dark Future Scale ( Zaleski et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%